Pitaya Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1068, a 9-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing pitaya in the home landscape. Tables include species of pitaya, varieties available in Florida, cultural practices by month and nutritional values. Published by the UF Department of Horticultural Sciences, November 2005.